2021
DOI: 10.3389/fpls.2021.666820
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Predictions With Nonadditive Effects Improved Estimates of Additive Effects and Predictions of Total Genetic Values in Pinus sylvestris

Abstract: Genomic selection study (GS) focusing on nonadditive genetic effects of dominance and the first order of epistatic effects, in a full-sib family population of 695 Scots pine (Pinus sylvestris L.) trees, was undertaken for growth and wood quality traits, using 6,344 single nucleotide polymorphism markers (SNPs) generated by genotyping-by-sequencing (GBS). Genomic marker-based relationship matrices offer more effective modeling of nonadditive genetic effects than pedigree-based models, thus increasing the knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…These contrasting results across studies for acoustic velocity is not unexpected given that the decomposition of genetic variance into additive and dominance components is population specific as it depends on the population allele frequencies ( Falconer and Mackay, 1996 ; Hill et al., 2008 ; Huang and Mackay, 2016 ). In full-sib or clonally replicated trials in other conifers, null or small dominance effects for wood traits were detected in Norway spruce ( Chen et al., 2019 , 2020 ; Nguyen et al., 2022 ) and in Scots pine ( Calleja-Rodriguez et al., 2021 ). In the well-studied Eucalyptus species and their hybrids, the genetic variance of wood density was found to be mostly additive ( Costa e Silva et al., 2004 , 2009 ; Resende et al., 2017 ; Tan et al., 2018 ; Thumma et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These contrasting results across studies for acoustic velocity is not unexpected given that the decomposition of genetic variance into additive and dominance components is population specific as it depends on the population allele frequencies ( Falconer and Mackay, 1996 ; Hill et al., 2008 ; Huang and Mackay, 2016 ). In full-sib or clonally replicated trials in other conifers, null or small dominance effects for wood traits were detected in Norway spruce ( Chen et al., 2019 , 2020 ; Nguyen et al., 2022 ) and in Scots pine ( Calleja-Rodriguez et al., 2021 ). In the well-studied Eucalyptus species and their hybrids, the genetic variance of wood density was found to be mostly additive ( Costa e Silva et al., 2004 , 2009 ; Resende et al., 2017 ; Tan et al., 2018 ; Thumma et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies attempted to decompose additive, dominance, and epistatic (ADE) variances using open-pollinated ( Gamal El-Dien et al., 2016 , 2018 ) or full-sib progeny trials ( Tan et al., 2018 ; Chen et al., 2019 ; Calleja-Rodriguez et al., 2021 ). However, for the studies and traits that showed considerable epistatic variances, it was always associated with large standard errors, and, in all but one case ( Gamal El-Dien et al., 2016 ), GBLUP-ADE was not the best model compared with GBLUP-AD or GBLUP-A based on AIC ( Gamal El-Dien et al., 2018 ; Tan et al., 2018 ; Calleja-Rodriguez et al., 2021 ). Although gene-gene interactions have been found to be pervasive in model organisms ( Mackay, 2014 ), there may be little power to detect epistatic variance for polygenic traits in practice ( Hill et al., 2008 ; Mäki-Tanila and Hill, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, incorporating non-additive, i.e.,, dominant and epistatic, effects into quantitative genetics modeling can improve heritability estimates and accuracy of genomic prediction (Su et al 2012;Wellmann and Bennewitz 2012;Kumar et al 2015;Xiang et al 2016). Limited empirical data exists for non-additive variance estimates, which varies greatly between organisms and can range from around 3-15% of total phenotypic variance in humans and animals (Misztal 1997;Zhu et al 2015) to a third or more in plants (Kumar et al 2015;Berguson et al 2017;Calleja-Rodriguez et al 2021). Adequate knowledge of non-additive genetic action is therefore of pivotal importance for a thorough understanding of the genetic architecture of complex traits, especially those that are fitness-related, and their evolutionary trajectory.…”
Section: Discussionmentioning
confidence: 99%